Heterogeneous parahydrogen induced polarization on Rh-containing silicalite-1 zeolites: effect of the catalyst structure on signal enhancement. Issue 14 (18th May 2022) - Wang, Weiyu; Sun, Qiming; Wang, Qiang; Li, Shenhui; Xu, Jun; Deng, Feng
Abstract : Parahydrogen-induced polarization (PHIP) on Rh-containing silicalite-1 catalysts is studied using both liquid-state and in situ magic angle spinning NMR techniques and the catalyst structure effect is revealed. Abstract : Rhodium-containing silicalite-1 zeolites are investigated by using a heterogeneous parahydrogen-induced polarization (HET-PHIP) NMR technique. Both liquid-state and in situ magic angle spinning (MAS) NMR experiments are performed to explore the PHIP effect on propene hydrogenation over different Rh-containing zeolites. The supported Rh species and zeolite structure determine the molecule polarization and signal enhancement. Intensive polarized signals are generated on the self-pillared Silicalite-1 nanosheets supported Rh catalyst, which can be correlated to ultrasmall Rh nanoparticles and the enhanced mass transport efficiency of the zeolite support. Silicalite-1 nanocrystals supporting large Rh nanoparticles on the external surface are less active for the generation of the PHIP. Single-atom Rh encaged in Silicalite-1 nanocrystals demonstrates high activity for the hydrogenation but low observed polarization generation efficiency, providing evidence on the critical role of the interactions between the zeolite confined polarized molecules and micropore structures in attenuating the polarization.